2017
DOI: 10.15376/biores.12.3.6789-6811
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Outdoor Bamboo-Fiber-Reinforced Composites with Different Densities

Abstract: aOutdoor bamboo-fiber-reinforced composites (OBFRCs) with four different densities were prepared, and the microstructure and physicomechanical properties of pristine samples were evaluated. In addition, the surface color, glossiness, roughness, water absorption, and wettability of the samples were tested to investigate the effects of panel density on the extent of surface weathering due to ultraviolet radiation. The results showed that the OBFRCs exhibited excellent physical and mechanical properties, which im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…On the other hand, the surface material of samples B-D is the coating main component, namely, the resin, so the photodegradation of the hydrophobic surface of samples B-D may be the major reason which results in a decrease in the water CA. The water CA of aged sample A shows a sharp deterioration after the water droplet stayed for 8 s on the sample surface, the rate of descent of aged sample A was greater than unaged sample A; a similar result was observed by Rao et al[1]…”
supporting
confidence: 84%
See 3 more Smart Citations
“…On the other hand, the surface material of samples B-D is the coating main component, namely, the resin, so the photodegradation of the hydrophobic surface of samples B-D may be the major reason which results in a decrease in the water CA. The water CA of aged sample A shows a sharp deterioration after the water droplet stayed for 8 s on the sample surface, the rate of descent of aged sample A was greater than unaged sample A; a similar result was observed by Rao et al[1]…”
supporting
confidence: 84%
“…The substrate OBS was prepared according to the standard procedure [1]. Four-year-old moso bamboo (Phyllostachys pubescens Mazel) culms were harvested at a plantation located in Anhui Province in eastern China.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the process of molding, the microstructure, chemical composition, physical and mechanical properties of bamboo, and resin have changed significantly. The results showed that the parenchyma, vessels, and fibers of bamboo were compacted to different degrees, and the cell walls were folded or even crushed [22,[45][46][47][48]. Phenolic resin was redistributed and cured under hygrothermal condition with high pressure, forming the macrobonding interface between the resin and the substrate surface, the microscale interface between the resin and the vessel as well as the cell cavity of parenchyma cells, and the nanoscale interface between the resin and the cell wall of parenchyma cells [49].…”
Section: Research Progress Of Bamboo Recombinationmentioning
confidence: 99%